Normal cognitive decline or dementia? - Ebmeier, K (2010)
Cognitive speed, inhibitory function, and memory decline with age while crystallised, particularly verbal, abilities remain largely intact. Poor health, fewer years of education, lower activity, the presence of the APOE E4 allele, and high BP appear to predict faster cognitive decline. Dementia is diagnosed in the presence of objective cognitive impairment, both long- and short-term memory, plus at least one additional (cortical) cognitive deficit, such as dysphasia, dyspraxia, agnosia, or disturbance in executive functioning. In addition, patients have to show significant impairment in social or occupational functioning and a significant decline from previous levels. Both smoking and diabetes increase the risk of all types of dementia, not smoking or even stopping smoking reduces this risk, but better control of type 2 diabetes does not appear to have a measurable effect. Drinking small to moderate amounts of alcohol appears to confer some benefit in ameliorating cognitive decline. There is some evidence that HRT, DHEA, BP lowering in patients without prior cerebrovascular disease, statins, vitamin B6 and procaine are NOT helpful. There is insufficient evidence to establish or refute a beneficial effect for exercise, treatment of type 2 diabetes, omega-3 fatty acids, folic acid with/without vitamin B12, antioxidant vitamins, or ginkgo biloba. Depressive symptoms are more prevalent than dementia. Clinical (major) depression can present with cognitive deterioration, often associated with subjective complaints. Patients with subjective or objective memory impairment, but without functional deterioration, can be referred to the local memory clinic, while demented patients eligible for acetylcholinesterase inhibitor treatment, patients whose diagnosis is unclear and who may need some specific investigations, as well as patients who may benefit from a combined approach with psychotropic drugs and behavioural support should be referred to the local mental health team.